High temperature increased lignin contents of poplar (Populus spp) stem via inducing the synthesis caffeate and coniferaldehyde - Zhao, Xianyan; Li, Panpan; Liu, Xingwang; Xu, Tianyu; Zhang, Yuqing; Meng, Haifeng; Xia, Tao (Frontiers in Genetics, 2022)
Lignin contributes to plant resistance to biotic and abiotic stresses and is dominantly regulated by enzymes which catalyze the generation of metabolites intermediates in lignin synthesis. However, the response of lignin and its key regulatory factors to high temperature stress are poorly understood. Here, this finding revealed that the content of lignin in poplar (Populus spp) stem increased after three days of high temperature stress treatment. In fourteen metabolic intermediates of lignin biosynthetic pathway with targeted metabolomics analysis, caffeate and coniferaldehyde increased evidently upon heat stress. C3’H (p-Coumaroylshikimate 3-hydroxylase) and CCR (Cinnamoyl-CoA reductase) are recognized to catalyze the formation of caffeate and coniferaldehyde, respectively. Transcriptome data and RT-qPCR (reverse transcription-quantitative real-time polymerase chain reaction) analysis uncovered the high transcriptional level of PtrMYBs (PtrMYB021, PtrMYB074, PtrMYB85, PtrMYB46), PtrC3’H1 (Potri.006G033300) and PtrCCR2 (Potri.003G181400), suggesting that they played the vital role in the increase of lignin and its metabolic intermediates were induced by high temperature. The discovery of key regulators and metabolic intermediates in lignin pathway that respond to high temperature provides a theoretical basis for quality improvement of lignin and the application of forest resources.